ANALISIS MUTU FISIK DAN KIMIA CABE JAWA (Piper retrofractum Vahl.) DENGAN METODE PENGERINGAN KABINET DAN PENJEMURAN MATAHARI - Asa Fauzan Muhammad; Rofandi Hartanto; Bara Yudhistira; Adhitya Pitara Sanjaya (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Cabe jawa is an Indonesian agricultural commodity that has been used by the community for consumtion and has many health benefits for the body. Cabe jawa contain alkaloid compounds such as piperonyl butylamine, silvatine, guinea imine, piperonylamine, filfiline, sitosterol and methylphenidate with the indentity component is piperine. The purpose of this study was to determine the effect of drying methods which are sun drying, cabinet drying at temperature set for 40oC., 50oC., 60oC. on physical quality (moisture content, ash content, color, volume and weight loss) and chemistry (piperine content) of cabe jawa and to know the difference in physical and chemical parameter between these drying mehods. This study used a completely randomized design (CRD), analyzed using the One Way ANOVA method with a significance level of 0,05. There is a significant difference in the quality parameter of piperine and redness, while there are no significant differences in the parameters of water content, ash content, volume loss and weight loss. The highest piperine content was in the sun drying method with a value of 2.86 and cabinet dryer 60oC with a value of 2.25; the highest redness was in the cabinet dryer method 40oC with a value of 11.77; The highest drying efficiency is in the 60oC cabinet dryer drying method with an efficiency value of 10.71%; the value of the moisture content obtained is in the range of 9-11%; the value of ash content is in the range 5.1 - 5.4%; the value of volume loss is in the range of 70% - 75% and the weight loss is in the range of 59% - 63%. The best drying method for Cabe jawa is cabinet dryer method at 60oC for 25 hours.